I walk with Vanessa : a story about a simple act of kindness - e uthor,e (New York : Schwartz & Wade Books, 2018)
An elementary school girl witnesses the bullying of another girl, but she is not sure how to help [in this wordless picture book].
School Library Journal starred, December 2017
Pub Weekly, December 2017
Booklist, November 2017
Kirkus Starred, December 2017
Horn Book, January 2018
K-3.
Keywords: Bullying -- Juvenile fiction; Schools -- Juvenile fiction; Friendship -- Juvenile fiction; Kindness -- Juvenile fiction; Stories without words; Bullies -- Fiction; Schools -- Fiction; Friendship -- Fiction; Kindness -- Fiction; Stories without words; Picture books